Structural and electronic analysis of the atomic scale nucleation of Ag on alpha-Ag2WO4 induced by electron irradiation - Andres, Juan; Gracia, Lourdes [UNESP]; Gonzalez-Navarrete, Patricio [UNESP]; Longo, Valeria M.; Avansi, Waldir; Volanti, Diogo P. [UNESP]; Ferrer, Mateus M.; Lemos, Pablo S.; La Porta, Felipe A. [UNESP]; Hernandes, Antonio C.; Longo, Elson [UNESP] (Nature Publishing Group, 2014)
In this work, we utilise a combination of theory, computation and experiments to understand the early events related to the nucleation of Ag filaments on alpha-Ag2WO4 crystals, which is driven by an accelerated electron beam from an electron microscope under high vacuum. The growth process and the chemical composition and elemental distribution in these filaments were analysed in depth at the nanoscale level using TEM, HAADF, EDS and XPS; the structural and electronic aspects were systematically studied in using first-principles electronic structure theory within QTAIM framework. The Ag nucleation and formation on alpha-Ag2WO4 is a result of the order/disorder effects generated in the crystal by the electron-beam irradiation. Both experimental and theoretical results show that this behavior is associated with structural and electronic changes of the [AgO2] and [AgO4] clusters and, to a minor extent, to the [WO6] cluster; these clusters collectively represent the constituent building blocks of alpha-Ag2WO4.